1997
DOI: 10.1182/blood.v89.10.3745.3745_3745_3754
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Anthracycline Accumulation in Doxorubicin-Selected U-937 Cells: Participation of Lysosomes

Abstract: The U-A10 cell line, a doxorubicin-selected variant of human U-937 myeloid leukemia cells, exhibits a redistribution of anthracyclines into a expanded vesicular compartment. The acidic nature of this compartment was confirmed by vital staining with a pH sensitive dye, LysoSensor yellow/blue DND-160. Identification of the vesicular compartment was performed by immunofluorescence analysis. Staining for the LAMP-1 and LAMP-2 antigens showed that the vesicles are enlarged lysosomes that are eccentrically placed ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 31 publications
0
64
0
Order By: Relevance
“…Although several authors have reported that anthracyclines can be detected in other acidic compartments, such as the trans-Golgi network or recycling endosomes [7,9,11], all of the fluorescent drugs tested have always been found solely in the more acidic lysosomal compartment of the various MDR cell lines analysed [7][8][9][10][11]. It has been suggested that the intracellular trapping of drugs in the expanded acidic organelle compartments of drug-resistant cells [10,26], plus the active drug export mediated by membranous ATP-dependent P-gps or MRPs, contributes to the reduced accumulation of drugs in MDR cells. Altan et al [11] have reported that lysosomes and recycling endosomes are not acidified in drug-sensitive MCF-7 breast tumour cells, and that the cytosol of drug-sensitive MCF-7 cells is more acidic than the cytosol of their drug-resistant MCF-7\ADR counterparts [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several authors have reported that anthracyclines can be detected in other acidic compartments, such as the trans-Golgi network or recycling endosomes [7,9,11], all of the fluorescent drugs tested have always been found solely in the more acidic lysosomal compartment of the various MDR cell lines analysed [7][8][9][10][11]. It has been suggested that the intracellular trapping of drugs in the expanded acidic organelle compartments of drug-resistant cells [10,26], plus the active drug export mediated by membranous ATP-dependent P-gps or MRPs, contributes to the reduced accumulation of drugs in MDR cells. Altan et al [11] have reported that lysosomes and recycling endosomes are not acidified in drug-sensitive MCF-7 breast tumour cells, and that the cytosol of drug-sensitive MCF-7 cells is more acidic than the cytosol of their drug-resistant MCF-7\ADR counterparts [11].…”
Section: Discussionmentioning
confidence: 99%
“…lysosomes and recycling endosomes) from drug-resistant MCF-7\ADR breast cancer cells, but not in those from their drug-sensitive MCF-7 counterparts exhibiting a vesicular acidification defect [11]. These authors and others have also shown that disruption of the pH gradient between the cytoplasm and the acidic organelles by a variety of lysosomotropic agents leads to the release of chemotherapeutic drugs accumulated in the acidic organelles from drug-resistant cells [10,11]. This intravesicular relocation of anthracyclines can obviously be expected to impair their cytotoxic action, which involves nuclear effects, including binding of DNA and interference with topoisomerase II [13].…”
Section: Inhibitors Of Vacuolar H T -Atpase Impair the Preferential Amentioning
confidence: 92%
See 2 more Smart Citations
“…In some mammalian cells, the morphology and transportation activities of the cellular acidic vesicles are strongly dependent on the pH gradients across the vesicular membranes (5–7). Several studies on multidrug‐resistant cells also implicate the correlation between intracellular pH gradients and cellular activity in expelling chemotherapeutic drugs to the endocytic vesicles (8–10). Moreover, neuronal disorders such as seizure and cytotoxic edema are reported to connect to pathologic changes of the pH in glial cells (11, 12).…”
mentioning
confidence: 99%